Anisotropic response of the moving vortex lattice in superconducting Mo(1-x)Gex amorphous films - Dolz, M.I.; Shalóm, D.E.; Pastoriza, H.; López, D.O. (Elsevier, 2012)
Fil: Dolz, M.I. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina